African Christian discourse redefining identity, literature and language education in Southern Africa: the case of the founding text of Paul Mwazha’s African Apostolic Church - Manyawu, Andrew T. (Faculty of Humanities: University of Lesotho, 2016)
Being both a subject and a medium of learning in Southern African schools, language is the vehicle through which society may pass on its worldview to its youths. This raises questions of selection and grading of material to be incorporated into syllabi and textbooks. This paper argues that Southern African language syllabi need a paradigm shift in order to better serve an African society seeking to reaffirm its identity after decades of oppression. There is need to more aggressively open up language curriculum to texts and discourses widely consumed by Africans but hitherto ignored by formal educational systems still biased towards Western worldview. These texts include founding the discursive production of African Instituted Churches. One such text is examined from the perspective of intertextuality in order to illustrate its literary and educational value. A case is then made for the inclusion of such texts onto secondary school curricula in Southern Africa.